Virtual Hematoxylin and Eosin Transillumination Microscopy Using Epi-Fluorescence Imaging - Giacomelli, Michael G.; Husvogt, Lennart; Vardeh, Hilde; Faulkner-Jones, Beverly E.; Hornegger, Joachim; Connolly, James L.; Fujimoto, James G. (PLOS ONE, 2016)
We derive a physically realistic model for the generation of virtual transillumination, white light microscopy images using epi-fluorescence measurements from thick, unsectioned tissue. We demonstrate this technique by generating virtual transillumination H&E images of unsectioned human breast tissue from epi-fluorescence multiphoton microscopy data. The virtual transillumination algorithm is shown to enable improved contrast and color accuracy compared with previous color mapping methods. Finally, we present an open source implementation of the algorithm in OpenGL, enabling real-time GPU-based generation of virtual transillumination microscopy images using conventional fluorescence microscopy systems.